Influence of Cd2+/S2− molar ratio and of different capping environments in the optical properties of CdS nanoparticles incorporated within a hybrid diureasil matrix - Gonçalves, Luís F. F. F. (2014)
The incorporation of CdS nanoparticles (NPs), as prepared through colloidal methods using reverse micelles, into diureasil hybrid organic-inorganic sol–gel matrices was investigated. Several experimental conditions, namely the influence of capping agent 3- mercaptopropyltrimethoxysilane (MPTMS) or the use of tetraethoxysilane (TEOS), were studied in order to assure the preservation of the original optical properties of colloidal CdS NPs after the incorporation of the NPs within the solid diureasil hybrid matrix. The diureasil matrix is based on a siliceous network cross linked through urea bonds to poly(oxyethylene)/poly(oxypropylene) (PEO/PPO) chains. The influence of the Cd2+/S2- molar ratio of the NPs in the stability and dispersion of the NPs within the diureasil matrix was also investigated. The obtained CdS doped hybrid matrix was characterized by absorption, steady-state and time-resolved photoluminescence (PL) spectroscopy and by transmission electron microscopy (TEM). The stability of the CdS NPs within the hybrid matrix showed to be dependent on the Cd2+/S2- molar ratio used in the synthesis of the NPs. The use of MPTMS proved to be crucial in the preservation of the original optical properties of the colloidal CdS NPs after the incorporation of the NPs within the hybrid matrix. The effect of MPTMS was in turn influenced by the Cd2+/S2- molar ratio employed in the synthesis of the CdS NPs. The use of MPTMS was less effective when Cd2+/S2- molar ratio equal to 0.5 was used. In the absence of MPTMS or TEOS larger NPs size distribution and clustering of the CdS NPs were obtained after the transfer of the NPs into the hybrid matrix.